Pulmonary Functional Imaging: Basics and Clinical Applications - Ohno, Yoshiharu; Hatabu, Hiroto; Kauczor, Hans-Ulrich (Springer International Publishing, 2021)
Anatomical Basis for Pulmonary Functional Imaging -- Pulmonary Function Tests -- Basics and Clinical Application of CT for Pulmonary Functional Evaluation -- Basics and Clinical Application of MR Assessment of Pulmonary Hemodynamics and Blood Flow -- Basics and Clinical Application of MR Assessment of Ventilation -- Principles and Clinical Applications of Respiratory Motion Assessment Using 4D Computed Tomography and Magnetic Resonance Imaging -- Pulmonary Functional Imaging, Basics and Clinical Application of Nuclear Medicine and Hybrid Imaging -- Functional Assessment of COPD -- Structure-Function Imaging of Asthma: Airway and Ventilation Biomarkers -- Functional Assessment of Cystic Fibrosis Lung Disease -- Functional Assessment of Pulmonary Venous Thromboembolism -- Multimodality Imaging of Pulmonary Hypertension: Prognostication of Therapeutic Outcomes -- Functional Assessment of Lung Cancer and Nodules -- Computational Approach Toward Pulmonary Functional Imaging -- Image-Based Phenotyping, Deep Learning (DL) and Artificial Intelligence (AI) Applications in Clinical and Research Radiology and Chest Imaging -- Future of Pulmonary Functional Imaging.